(untitled) (Global Journal of Science Frontier Research, 2018)
The snowmelt runoff is foundation to various resource based economics i.e. Agriculture, Tourism, Horticulture and Hydropower. The Glacier in the Himanchal Pradesh Himalayas have been reported to be receding rapidly due to the global climate change. Due to its economic and scientific importance, it is mandatory to access theses resources and its release is essential to predict the flow during the snowmelt period. The essence of this study is to invent and develop a model for pragmatic purpose. The Snowmelt runoff model (SRM) has been widely used in simulation and forecasting daily streamflow in mountain basin where snowmelt is a major runoff factor. A degree day approach for the snowmelt runoff modelling is used here which integrates the input from Remote sensing data and metrological data including the parameter i.e. runoff coefficient, degree day factor, temperature lapse rate, critical temperature, rainfall contributing area and recession coefficient.